Brumptomyia carvalheiroi sp. nov. (Diptera: Psychodidae: Phlebotominae) from Atlantic forest domain, São Paulo State, Brazil - Shimabukuro, Paloma Helena Fernandes; Marassá, Ana Maria; Galati, Eunice Aparecida Bianchi (Zootaxa, 2007)
Brumptomyia carvalheiroi sp. nov. (Diptera, Psychodidae: Phlebotominae) from Ribeira Valley, São Paulo State, Brazil is described and illustrated. This new taxon is morphologically similar to Brumptomyia mangabeirai (Barretto & Coutinho, 1941).